USING CHAIN CARD GAME TO IMPROVE THE WRITING SKILL OF THE SIXTH GRADE SD KARTIKA IV-1 MALANG - Iflinda Virgina Sutalistya (Journey: Journal of English Language and Pedagogy, 2018)
Based on the implementation of Class Action Research (CAR) by using strategy of chain card game, there are detailed description for each cycle. In cycle I the students who has mastered the learning progress achieve 60% with the score average is 73,3. For the learning activities there is 2 complete descriptors with the percentage of 85% and 3 incomplete descriptors with the percentage of 47,8%. For creativity there are 2 complete descriptors with the percentage of 85% and 2 incomplete descriptors with the percentage of 55%. For the Students’ pleasant all off the descriptors are complete with the percentage of 93,3%. The interactivity of the students show that all the descriptors are complete with the percentage of 85,5%. There is an increasing of score that achieved by students who has mastered the learning. That is 80% with the average is 81,0. For the learning activities all of the descriptors are complete with the percentage of 94%. There is an increasing of 9,0%. For the interactivity all of the descriptors are complete with percentage of 89,1%. There is an increasing of 4,1%. For the students’ pleasant 100% are the descriptors are complete. There is an increasing of 6,7%. For Interactivity, all of the descriptors also complete with the percentage of 96,7%. There is an increasing of 11,2%. Considering the data above, the implementation of chain card game can improve the students writing skill of sixth grade at SD Kartika IV-1 Malang